The Influenza A Virus M2 Protein trans-Complementation System Offers a Set of Tools for the Undergraduate Virology Laboratory - Michael L. Grantham (American Society for Microbiology, 2019)
An authentic, hands-on experience in the laboratory is an important part of any undergraduate biology course. However, there are a limited number of mammalian virus systems that students can work with safely in an undergraduate teaching laboratory. For many systems, the risk to the students is too high. The influenza A virus M2 protein trans-complementation system bridges this gap. This system consists of a virus with mutations that prevent the expression of the essential M2 protein; therefore this virus can only replicate in a cell line that provides M2 in trans. Here, we describe the use of this system to carry out hemagglutination, real-time reverse transcriptase PCR, 50% tissue culture infectious dose, and plaque assays in an undergraduate lab setting.